Deficit residential housing publica or deficit again? About housing conditions of dwellings by public policy and sustainability (ARQUISUR Revista, 2014)
This article presents a conceptual reflection concerning the notion of housing deficit and the need to incorporate sustainability aspects seeking to alleviate the shortcomings, in housing, presents the Republic Argentina as a whole.Intends to reflect on solutions, which are made from our institutions of Government housing to the popular sectors, and what are the legal instruments used for the realization of them.Starting to understand the housing deficit not as the mere lack of housing - object, but in relation to the whole of the city and the principles of building and urban sustainability/unsustainability that generate, we will ask if these solutions do not immerse us in the vicious cycle of spending deficit to one even greater deficit
Keywords: housing shortage; rights and regulations; federal housing plan; building sustainability and urban; social housing